Tribakti - Institut Agama Islam Tribakti Lirboyo Kediri
Articles that discuss Islamic studies and thoughts which include culture, social, education, politics, law, economics, and communication.
Keywords: Islam : Periodicals; Islamic education : Periodicals; Islamic education; Islam